Peran Budaya Populer dalam Memperkuat Identitas Nasional Indonesia di Era Globalisasi - Akbar Lubis, Hana' Fairuz; Putri, Shavira Melanie (Universitas Indo Global Mandiri, 2024)
In the era of globalization, popular culture has been a tool in understanding the complexity of international relations due to its easy access and simple packaging through technological advances. Globalization and the influx of other foreign cultures have been posing some threats and challenges in shifting national culture and values. The phenomenon of the influx of foreign cultures such as hallyu and westernization in Indonesia is slowly threatening Indonesia's national identity. Using the lens of Pop Culture and World Politics (PCWP) and Cultural Resistance from Antonio Gramsci (1971), the author examines in depth how the role of popular culture produced by Indonesian filmmakers and musicians can answer the challenges to the shift in Indonesia's national identity through cultural expression to oppose the dominant forces in the era of globalization at the international level. This research uses qualitative and descriptive methods in examining film and music artefacts produced by Indonesian filmmakers and musicians which are gaining international attention. The findings of this study aim to reveal that in the era of globalization, films and music produced by Indonesian filmmakers and musicians as the non-state actors play an important role in answering the challenges to the domination of foreign cultures in the context of maintaining Indonesia's original culture and identity by producing films and music containing local elements that are recognized and consumed by international audiences.